O portfólio como instrumento didático-metodológico no processo avaliativo de Ciências da Natureza na educação de jovens e adultos - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This research had as general objective to understand the contributions and limitations of the portfolio in the evaluation process of the Teaching of Natural Sciences in the Education of Young and Adults (EJA). Specifically, it sought to: develop evaluative activities, through the portfolio, in an EJA class in the curricular components of Biology, Physics and Chemistry; Analyze the students' perception of the use of the portfolio as an evaluation tool; And verify if the concepts presented in the activities of the portfolio correspond to the scientific concepts worked in class by the researcher. Methodologically, it was characterized as a participant research, presenting exploratory / explanatory character and qualitative approach (GIL, 2002). For the data collection a portfolio was built during the Supervised Internship of the Degree in Natural Sciences, containing the following evaluation instruments: textual production, interpretation of cartoons, debates, experimentation, research, among others. The analysis of the results was based on the content analysis of Bardin (1977). The conceptions about EJA are corroborated by Arroyo (2005, 2007), Brunel (2014), Freire (1991, 1993, 2011), Garcia (2011), Pinto (1984), Soares & Galvão (2005) and Souza The conceptions of Portfolio by Alvarenga (2001), Sá-Chaves (2000), Shores & Grace (2001) and Vieira (2006). During the research it was verified that the portfolio, as a didactic-methodological instrument in the Teaching of Natural Sciences, constitutes as a formative evaluation tool, that allows the teacher to follow the conceptual development of the student in a procedural way, re-planning when necessary. Whereas, for the student develops autonomy and creativity, as it becomes the protagonist of the educational process. It is concluded that the portfolio contributes to a formative education, respecting the cultural plurality.
Keywords: Avaliação; Ensino de Ciências da Natureza; Análise de conteúdo; Educação de jovens e adultos; Teach; Youth and adult education; Biologia; Física; Química; Biology; Chemistry; Physical; CNPQ::CIENCIAS EXATAS E DA TERRA